Reference values of 24-hour, day-time and nocturnal glucose variability parameters in subjects with normal glucose tolerance - Ju. F. Semenova; V. V. Klimontov (Сахарный диабет)
BACKGROUND: Glucose variability (GV) is recognized as a risk factor for microvascular and macrovascular complications of diabetes and hypoglycemia. A number of indices have been proposed to assess GV, but there are no generally accepted normal reference values for these indices.AIM: To establish the reference values of 24-hour, day-time and nocturnal GV parameters derived from continuous glucose monitoring (CGM) data in young and middle-aged subjects with normal glucose tolerance.MATERIALS AND METHODS: A blind 6–7-day CGM was performed in 50 subjects, 20 men and 30 women, aged from 22 to 56 years, with normal values of the oral glucose tolerance test and glycated hemoglobin A1c. GV parameters: Standard Deviation (SD), Coefficient of Variation (CV), Mean Amplitude of Glycemic Excursions (MAGE), 2-hour Сontinuous Overlapping Net Glycemic Action (CONGA), Lability Index (LI), J-index, Mean Absolute Glucose rate of change (MAG), М-value, High Blood Glucose Index (HBGI), Low Blood Glucose Index (LBGI) were calculated for 24-hour records, day-time (6.00–23.59) and night (0.00–5.59) hours.RESULTS: 95% confidence intervals for 24-hour records were: mean glucose 5.2–6.6 mmol/L, SD 0.5–1.3 mmol/L, CV 9.1–23.2%, MAGE 1.2–3.2 mmol/L, CONGA 4.3–5.9 mmol/L, MAG 0.5–2.1 mmol×L-1×h-1, LI 0.1–1.3 (mmol/L)2×h-1, J-index 11.3–18.6 (mmol/L)2, M-value 0.4–4.4, HBGI 0.1–1.9, LBGI 0.3–3.2.The following day-time values were estimated: mean glucose 5.3–6.7 mmol/L, SD 0.5–1.4 mmol/L, CV 8.7–24.5%, MAGE 1.2–3.4 mmol/L, CONGA 4.3–5.9 mmol/L, MAG 0.6–2.5 mmol×L-1×h-1, LI 0.2–1.6 (mmol/L)2×h-1, J-index 11.2–19.6 (mmol/L)2, M-value 0.2–3.8, HBGI 0.1–1.9, LBGI 0.3–3.0. The values for nocturnal hours were: mean glucose 4.7–6.4 mmol/L, SD 0.3–0.9 mmol/L, CV 5.3–17.9%, MAGE 0.7–2.7 mmol/L, CONGA 4.1–5.8 mmol/L, MAG 0.3–1.8 mmol×L-1×h-1, LI 0.05–0.8 (mmol/L)2×h-1, J-index 8.5–17.5 (mmol/L)2, M-value 0.2–5.2, HBGI 0–0.9, LBGI 0.3–3.6.CONCLUSION: The obtained reference values of the GV indices should be taken into account in research and in clinical practice when interpreting the results of CGM in young and middle-aged people.